Stoppard's theatre : finding order amid chaos - Fleming, John (John Patrick), 1965- (Literary modernism series., 2001)
"With a thirty-year run of award-winning, critically acclaimed, and commercially successful plays, from Rosencrantz and Guildenstern are Dead (1967) to The Invention of Love (1997), Tom Stoppard is arguably the preeminent playwright in Britain today. His popularity also extends to the United States, where his plays have won three Tony awards and his screenplay for Shakespeare in Love won the 1998 Academy Award for Best Original Screenplay." "In this volume, John Fleming offers the first book-length assessment of Stoppard's work in nearly a decade. He takes an in-depth look at the three newest plays (Arcadia, Indian Ink, and The Invention of Love) and the recently revised versions of Travesties and Hapgood, as well as at four other major plays (Rosencrantz, Jumpers, Night and Day, and The Real Thing). Drawing on Stoppard's personal papers at the University of Texas Harry Ransom Humanities Research Center (HRHRC), Fleming also examines Stoppard's previously unknown play Galileo, as well as numerous unpublished scripts and variant texts of his published plays."--Jacket